Web 1.0 to Web 2.0: an observational study and empirical evidence for the historical r(evolution) of the social web. (2017) - Sykora, Martin
Applications such as Twitter, Facebook or Youtube have taken the internet community by storm and have literally initiated a revolution in online communication. These social media applications are also often referred to by the general, somewhat vague but yet eloquent term - Web 2.0. The term implies a perceived second generation of World Wide Web, i.e., Web 1.0 → Web 2.0. Nevertheless the reference to a 'second' version of the web is misleading, since there was not any specific technical update of the World Wide Web. Hence, this paper empirically explores social media in a historical context as it has evolved and driven a revolution in online communication over the last decade. A unique historical dataset, made available by the Wayback Machine Internet Archive project is employed in order to provide an accurate historical record of the primary web design and related elements that drove the evolution towards a more social and interactive web. This study presents a unique contribution to related academic literature.